A Needs Analysis for the Improvement of the Students’ Communicative Competence; A Syllabus design for Speaking 1 Course at English Department Sawerigading University - Syamsuddin Syamsuddin; Jamaluddin Al Afgani (Universitas Sulawesi Barat, 2019)
Each learner has different needs in learning, as well as the students at the English Department Sawerigading University Makassar. This study aims at determining the effectiveness of a needs analysis to design a syllabus for the speaking 1 course to enhance the students’ communicative competence. Research and Development Methods (R & D) are used with three systematic steps: input, development, and output. The input step begins with a needs analysis (NA) involving 40 respondents who are chosen purposively. The data are collected through NA questionnaires and they are analyzed descriptively. Development Step is made to formulate the objectives and course targets that are then used to determine the course subject of speaking 1. The output step is done to design lesson plans and prototype of teaching materials. This study has found a teaching material development methodology that has resulted lesson plans and prototypes for a unit of instruction-based resource needs. This methodology can be used by designers or lecturers to develop other English teaching materials in various courses.